Construction waste recycled aggregate concrete and preparation method thereof
Through the combination of modified regenerated aggregate and polyacrylonitrile fibers, the problem of poor mechanical properties of regenerated concrete is solved, and the compressive strength and crack resistance of concrete are significantly improved.
Patent Information
- Application Number
- CN202411916663.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-24
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-24
AI Technical Summary
The mechanical properties of recycled concrete are poor, mainly due to the poor bonding performance between it and cement mortar on the surface of recycled aggregate.
The regenerated aggregate is activated by strong acid treatment and nanocellulose suspension impregnation reaction using modified regenerated aggregate and polyacrylonitrile fibers, and the regenerated aggregate is modified with alkylkone dimers to improve its compatibility and reactivity with the hydrated product.
The mechanical properties of concrete are significantly improved, including compressive strength and crack resistance, by improving the structure of the interface transition zone and enhancing the tightness between the phases.
Smart Images

Figure BDA0005206975110000081 
Figure BDA0005206975110000091
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of concrete, and more specifically, to a construction waste recycled aggregate tailings concrete and a preparation method thereof. Background Art
[0002] With the acceleration of global urbanization, the construction industry has ushered in unprecedented development opportunities, but it is also facing the dual challenges of resource consumption and environmental pressure. As an indispensable basic material in the construction field, the demand for concrete continues to grow, but the natural aggregate resources used in its preparation process are becoming increasingly exhausted. At the same time, the amount of construction waste generated has also increased sharply. Among construction waste, waste concrete accounts for a considerable proportion. These waste concretes are often regarded as useless and are randomly piled up or landfilled, which not only occupies precious land resources, but also may cause pollution to the surrounding environment, such as soil pollution, water pollution and air pollution. However, from another perspective, waste concrete is actually a potential and recyclable resource. Through advanced crushing, screening and reprocessing technologies, waste concrete can be converted into recycled aggregates, which can then be used to prepare recycled concrete, realizing the effective circulation and reuse of resources.
[0003] As an environmentally friendly and sustainable building material, the preparation and application of recycled aggregate concrete has significant environmental and social benefits. However, compared with natural aggregate, recycled aggregate has some shortcomings in performance. Due to the presence of more cracks and defects on the surface of recycled aggregate, the bonding performance between it and cement mortar is poor, which in turn affects the mechanical properties of recycled concrete. Summary of the invention
[0004] In order to improve the mechanical properties of recycled concrete, the present application provides a construction waste recycled aggregate concrete and a preparation method thereof.
[0005] In the first aspect, the present application provides a construction waste recycled aggregate concrete, which adopts the following technical solution: A construction waste recycled aggregate concrete, comprising the following raw materials in parts by weight: 15-20 parts of modified recycled aggregate, 3-5 parts of polyacrylonitrile fiber, 0.2-0.4 parts of polycarboxylic acid-based high-efficiency water reducing agent, 2-4 parts of calcium silicate, 26-30 parts of cement, 16-22 parts of water, and 8-10 parts of crushed stone. The modified recycled aggregate is recycled aggregate modified by alkyl ketene dimer.
[0006] By adopting the above technical solution, the structure of the old interface transition zone of recycled concrete is loose and there are many holes. After adding an appropriate amount of polyacrylonitrile fiber, the cement hydration degree, microstructure density and element content distribution uniformity at the new interface are improved. The appropriate amount of fiber plays a positive role in the uniform distribution and full reaction of water molecules between cement particles during the curing stage, and the fiber can form a relatively dense network structure with the cement hydration product, enhancing the compactness between the phases. The recycled aggregate is further modified using alkyl ketene dimer to improve the compatibility and reactivity between the recycled aggregate and the hydration product, and to improve the strength of the interface transition zone. At the same time, the modified recycled aggregate is used in concrete to exert its good compressive strength and further improve the mechanical properties of concrete.
[0007] Optionally, the preparation of the modified recycled aggregate comprises the following steps: (1) using strong acid to soak the regenerated aggregate to obtain acidified regenerated aggregate, washing and drying the regenerated aggregate, adding the nanocellulose suspension to react for 2-3 hours to obtain activated regenerated aggregate; (2) The resin material and the alkyl ketene dimer are uniformly mixed and dispersed in water, and the activated recycled aggregate is placed in the mixture for stirring reaction for 2-3 hours. After natural air drying and curing, the mixture is ground and sieved to obtain the modified recycled aggregate.
[0008] By adopting the above technical scheme, after the regenerated aggregate is activated by strong acid treatment, a nanocellulose suspension is introduced for stirring reaction, and the high specific surface area and CSH gel nucleation sites of nanocellulose are used to stimulate the volcanic ash effect of the regenerated aggregate and generate additional CSH gels. These gels accumulate to form a 3D skeleton network, strengthen the internal microstructure of the regenerated aggregate, and enhance the cohesion between the regenerated aggregate and the cement hydration product through nano-bridging. At the same time, the added alkyl ketene dimer reacts with the active hydroxyl groups on the nanocellulose to form a stable covalent bond film covering the surface of the regenerated aggregate. This film can not only form a strong chemical bond with other components in the concrete raw materials, but also significantly improve the interfacial compatibility between the regenerated aggregate and the mortar, thereby comprehensively improving the performance of the regenerated aggregate in cement-based materials.
[0009] Optionally, the weight ratio of the recycled aggregate to the resin material, the powder and the alkyl ketene dimer added during the modification process is 2:1-1.2:0.2:0.1-0.5; The mass concentration of the nanocellulose suspension is 2-3 g / L.
[0010] Optionally, 0.2-0.4 parts of rare earth ferrosilicon powder are also added in step (2).
[0011] By adopting the above technical solution, the rare earth elements and ferrosilicon alloy in rare earth ferrosilicon powder can refine the grains in the recycled aggregate and improve its microstructure. This refinement helps to reduce defects and stress concentration points in the aggregate, thereby improving its mechanical properties such as compressive strength and toughness, and further improving the ability of the recycled aggregate to resist deformation and damage, thereby showing higher mechanical properties.
[0012] Optionally, the particle size of the modified recycled aggregate is 5-10 mm.
[0013] Optionally, the resin material is polyurethane resin.
[0014] By adopting the above technical scheme, the isocyanate and hydroxyl groups contained in the polyurethane can react with the hydroxyl groups on the surface of the modified recycled aggregate to form polyurethane chemical bonds, thereby further strengthening the connection between the modified recycled aggregate and the remaining raw materials of the concrete and improving the interface compatibility. At the same time, it can better resist deformation and damage when subjected to external forces, thereby improving the mechanical properties of the concrete.
[0015] Optionally, 1-3 parts of admixture material are added to the raw materials, and the admixture material is any one of slag, volcanic ash or fly ash.
[0016] By adopting the above technical solution, these industrial materials with certain activity can continuously fill the calcium hydroxide in the interface transition zone between the recycled aggregate and the mortar to react and generate new products to fill the pores, thereby improving the pore structure of the microstructure at the interface and increasing the density.
[0017] In the first aspect, the present application provides a method for preparing construction waste recycled aggregate concrete, using the following technical solution: A method for preparing construction waste recycled aggregate concrete comprises the following steps: (1) weighing various raw material components, adding cement, crushed stone, calcium silicate and half of the water, and mixing and stirring to obtain a primary mixture; (2) Adding modified recycled aggregate, polycarboxylic acid-based high-efficiency water reducing agent, polyacrylonitrile fiber and the remaining water into the primary mixture and stirring to obtain the construction waste recycled aggregate concrete.
[0018] In summary, this application has the following beneficial effects: 1. This application significantly improves the mechanical properties of concrete by incorporating polyacrylonitrile fiber and modified recycled aggregate. Polyacrylonitrile fiber can form a dense network structure to enhance the crack resistance and toughness of concrete; while the modified recycled aggregate significantly improves the compressive strength and crack resistance of concrete by optimizing the internal microstructure and improving the interface compatibility.
[0019] 2. In the present application, nanocellulose and alkyl ketene dimer are preferably used to modify the recycled aggregate. Nanocellulose can react with substances in the recycled aggregate and adhere to the surface of the recycled aggregate, while alkyl ketene dimer can interact with nanocellulose to form a film that adheres to the surface of the recycled aggregate and reacts with the remaining raw materials in the concrete raw materials. The added rare earth ferrosilicon powder can penetrate into the cracks of the recycled aggregate, repair the pores, improve the microstructure, and be added to the concrete to further improve the compression and crack resistance of the concrete.
[0020] 3. The method of the present application uses a large amount of modified recycled aggregates, which are derived from construction waste. Through scientific modification and treatment, the waste is reused and the exploitation of new natural resources is reduced. DETAILED DESCRIPTION
[0021] The present application is further described in detail below with reference to the embodiments.
[0022] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased commercially.
[0023] Portland cement was purchased from Sanhe Yanhong Trading Co., Ltd., with the product number ZP-001; nanocellulose was purchased from Wuhan Lvjing Fenghua Biotechnology Co., Ltd., with the model number CB2311; polyurethane was purchased from Laiyang Shengbang Silicone Technology Co., Ltd., with the model number SI-2045; alkyl ketene dimer was purchased from Shandong Haoyao New Materials Co., Ltd., with the model number HY1541; crushed stone was obtained by mixing crushed stone with a particle size of 5 mm to 10 mm and crushed stone with a particle size of 10 mm to 20 mm in a mass ratio of 3:17; epoxy resin was purchased from Langfang Nanze Anticorrosive Materials Co., Ltd., with the brand name E-44; polyacrylonitrile fiber length was 1-2 mm; volcanic ash was purchased from Shijiazhuang Tourmaline Mineral Products Co., Ltd., with a bulk density of 4450 kg / m 3 ; Slag was purchased from Lingshou County Changwang Mineral Products Processing Plant, item number A201902; fly ash was purchased from Lingshou County Shuangshi Mineral Products Processing Plant, density 2.65g / cm 3 .
[0024] Preparation examples of raw materials and / or intermediates Preparation Example 1 A modified recycled aggregate, the preparation of which comprises the following steps: (1) taking nanocellulose and placing it in water at a controlled temperature of 10° C. and ultrasonically treating it for 30 min to obtain a nanocellulose suspension with a mass concentration of 2 g / L, adding 20 kg of regenerated aggregate into a mixed strong acid of sulfuric acid and nitric acid in a ratio of 3:1, ultrasonically immersing it for 2 h, washing it with water, drying it, and then adding it into the nanocellulose suspension and immersing it for 2 h to obtain an activated regenerated aggregate; (2) 10 kg of polyurethane and 3 kg of alkyl ketene dimer were evenly mixed and dispersed in 20 kg of water. The activated recycled aggregate was placed in the mixture for stirring reaction for 3 h. After natural air drying and curing, the mixture was ground and sieved to obtain a modified recycled aggregate with a particle size of 5-10 mm.
[0025] Preparation Example 2 A modified recycled aggregate, the preparation of which comprises the following steps: (1) taking nanocellulose and placing it in water at a controlled temperature of 10° C. and ultrasonically treating it for 30 min to obtain a nanocellulose suspension with a mass concentration of 2 g / L, adding 20 kg of regenerated aggregate into a mixed strong acid of sulfuric acid and nitric acid in a ratio of 3:1, ultrasonically immersing it for 3 h, washing it with water, drying it, and then adding it into the nanocellulose suspension and stirring it for 2 h to obtain an activated regenerated aggregate; (2) 11 kg of polyurethane and 1 kg of alkyl ketene dimer were uniformly mixed and dispersed in 20 kg of water, and the activated recycled aggregate was immersed in the reaction for 8 hours, and then naturally air-dried and solidified to obtain the modified recycled aggregate.
[0026] Preparation Example 3 A modified recycled aggregate, the preparation of which comprises the following steps: (1) Nanocellulose was placed in water at a controlled temperature of 10° C. and subjected to ultrasonic treatment for 30 min to obtain a nanocellulose suspension with a mass concentration of 2 g / L; 20 kg of regenerated aggregate was added to a mixed strong acid of sulfuric acid and nitric acid in a ratio of 3:1, and ultrasonically immersed for 2.5 h; the aggregate was washed with water, dried, and then added to the nanocellulose suspension and stirred for reaction for 2 h to obtain an activated regenerated aggregate; (2) 12 kg of polyurethane and 5 kg of alkyl ketene dimer were uniformly mixed and dispersed in 20 kg of water, and the activated recycled aggregate was immersed in the reaction for 7.5 hours, and then taken out and naturally air-dried and solidified to obtain the modified recycled aggregate.
[0027] Preparation Example 4 A modified recycled aggregate, which is different from Preparation Example 1 in that the resin material added in this Preparation Example is epoxy resin.
[0028] Preparation Example 5 A modified recycled aggregate, which is different from Preparation Example 1 in that 0.2 kg of rare earth ferrosilicon powder is further added in this Preparation Example, and the preparation comprises the following steps: (1) taking nanocellulose and placing it in water at a controlled temperature of 10° C. and ultrasonically treating it for 30 min to obtain a nanocellulose suspension with a mass concentration of 2 g / L, adding 20 kg of regenerated aggregate into a mixed strong acid of sulfuric acid and nitric acid in a ratio of 3:1, ultrasonically immersing it for 2 h, washing it with water, drying it, and then adding it into the nanocellulose suspension and immersing it for 2 h to obtain an activated regenerated aggregate; (2) 10 kg of polyurethane, 0.2 kg of rare earth ferrosilicon powder and 3 kg of alkyl ketene dimer were evenly mixed and dispersed in 20 kg of water. The activated recycled aggregate was stirred and reacted for 3 hours. After natural air drying and curing, it was ground and sieved to obtain a modified recycled aggregate with a particle size of 5-10 mm.
[0029] Preparation Example 6 A modified recycled aggregate, which is different from Preparation Example 1 in that 0.3 kg of rare earth ferrosilicon powder is further added in this Preparation Example, and the preparation comprises the following steps: (1) taking nanocellulose and placing it in water at a controlled temperature of 10° C. and ultrasonically treating it for 30 min to obtain a nanocellulose suspension with a mass concentration of 2 g / L, adding 20 kg of regenerated aggregate into a mixed strong acid of sulfuric acid and nitric acid in a ratio of 3:1, ultrasonically immersing it for 2 h, washing it with water, drying it, and then adding it into the nanocellulose suspension and immersing it for 2 h to obtain an activated regenerated aggregate; (2) 10 kg of polyurethane, 0.3 kg of rare earth ferrosilicon powder and 3 kg of alkyl ketene dimer were mixed evenly and dispersed in 20 kg of water. The activated recycled aggregate was stirred and reacted for 3 hours. After natural air drying and curing, it was ground and sieved to obtain a modified recycled aggregate with a particle size of 5-10 mm.
[0030] Preparation Example 7 A modified recycled aggregate, which is different from Preparation Example 1 in that 0.4 kg of rare earth ferrosilicon powder is further added in this Preparation Example, and the preparation comprises the following steps: (1) taking nanocellulose and placing it in water at a controlled temperature of 10° C. and ultrasonically treating it for 30 min to obtain a nanocellulose suspension with a mass concentration of 2 g / L, adding 20 kg of regenerated aggregate into a mixed strong acid of sulfuric acid and nitric acid in a ratio of 3:1, ultrasonically immersing it for 2 h, washing it with water, drying it, and then adding it into the nanocellulose suspension and immersing it for 2 h to obtain an activated regenerated aggregate; (2) 10 kg of polyurethane, 0.4 kg of rare earth ferrosilicon powder and 3 kg of alkyl ketene dimer were mixed evenly and dispersed in 20 kg of water. The activated recycled aggregate was stirred and reacted for 3 hours. After natural air drying and curing, it was ground and sieved to obtain a modified recycled aggregate with a particle size of 5-10 mm.
[0031] Comparative Preparation Example 1 A modified recycled aggregate, which is different from Preparation Example 1 in that the nanocellulose suspension is not used to activate the recycled aggregate in this Preparation Example, specifically comprising the following steps: (1) 20 kg of recycled aggregate was added into a mixed strong acid of sulfuric acid and nitric acid in a ratio of 3:1, and ultrasonically immersed for 2 h. After washing with water and drying, the recycled aggregate was immersed in water for 2 h to obtain the recycled aggregate. (2) 10 kg of polyurethane and 3 kg of alkyl ketene dimer were evenly mixed and dispersed in 20 kg of water. The above-mentioned recycled aggregate was stirred and reacted for 3 hours. After natural air drying and curing, it was ground and sieved to obtain a modified recycled aggregate with a particle size of 5-10 mm.
[0032] Comparative Preparation Example 2 A modified recycled aggregate, which is different from Preparation Example 1 in that the recycled aggregate is not treated with alkyl ketene dimer in this Preparation Example, specifically comprises the following steps: (1) taking nanocellulose and placing it in water at a controlled temperature of 10° C. and ultrasonically treating it for 30 min to obtain a nanocellulose suspension with a mass concentration of 2 g / L, adding 20 kg of regenerated aggregate into a mixed strong acid of sulfuric acid and nitric acid in a ratio of 3:1, ultrasonically immersing it for 2 h, washing it with water, drying it, and then adding it into the nanocellulose suspension and immersing it for 2 h to obtain an activated regenerated aggregate; (2) Disperse 10 kg of polyurethane in 20 kg of water, add the activated recycled aggregate and stir to react for 3 hours, naturally air dry and solidify, then grind and sieve to obtain modified recycled aggregate with a particle size of 5-10 mm. Example
[0033] Example 1 A construction waste recycled aggregate concrete, the preparation of which comprises the following steps: (1) Weighing the raw material components, adding 26 kg of cement, 9 kg of crushed stone, 3 kg of calcium silicate and 10 kg of water, and mixing to obtain a primary mixture; (2) Add 17.5 kg of the modified recycled aggregate prepared in Preparation Example 1, 0.3 kg of a polycarboxylic acid-based high-efficiency water reducing agent, 4 kg of polyacrylonitrile fiber and the remaining 10 kg of water to the primary mixture and mix well to obtain the construction waste recycled aggregate concrete.
[0034] Example 2 A construction waste recycled aggregate concrete, the preparation of which comprises the following steps: (1) Weighing the raw material components, adding 28 kg of cement, 10 kg of crushed stone, 2 kg of calcium silicate and 8 kg of water, and mixing to obtain a primary mixture; (2) Add 15 kg of the modified recycled aggregate prepared in Preparation Example 3, 0.4 kg of a polycarboxylic acid-based high-efficiency water reducing agent, 5 kg of polyacrylonitrile fiber and the remaining 8 kg of water to the primary mixture and mix well to obtain the construction waste recycled aggregate concrete.
[0035] Example 3 A construction waste recycled aggregate concrete, the preparation of which comprises the following steps: (1) Weighing the raw material components, adding 30 kg of cement, 8 kg of crushed stone, 4 kg of calcium silicate and 11 kg of water, and mixing and stirring to obtain a primary mixture; (2) Add 20 kg of the modified recycled aggregate prepared in Preparation Example 2, 0.2 kg of a polycarboxylic acid-based high-efficiency water reducing agent, 3 kg of polyacrylonitrile fiber and the remaining 11 kg of water to the primary mixture and mix well to obtain the construction waste recycled aggregate concrete.
[0036] Example 4 A construction waste recycled aggregate concrete, which is different from Example 1 in that the modified recycled aggregate added in this example is prepared in Preparation Example 4.
[0037] Example 5 A construction waste recycled aggregate concrete, which is different from Example 1 in that the modified recycled aggregate added in this example is prepared in Preparation Example 5.
[0038] Example 6 A construction waste recycled aggregate concrete, which is different from Example 1 in that the modified recycled aggregate added in this example is prepared in Preparation Example 6.
[0039] Example 7 A construction waste recycled aggregate concrete, which is different from Example 1 in that the modified recycled aggregate added in this example is prepared in Preparation Example 7.
[0040] Example 8 A construction waste recycled aggregate concrete, which is different from Example 1 in that 1 kg of volcanic ash is further added to the raw materials of this example, and the preparation includes the following steps: (1) Weighing various raw material components, adding 26 kg of cement, 9 kg of crushed stone, 1 kg of volcanic ash, 3 kg of calcium silicate and 10 kg of water, and mixing and stirring to obtain a primary mixture; (2) Add 17.5 kg of the modified recycled aggregate prepared in Preparation Example 1, 0.3 kg of a polycarboxylic acid-based high-efficiency water reducing agent, 4 kg of polyacrylonitrile fiber and the remaining 10 kg of water to the primary mixture and mix well to obtain the construction waste recycled aggregate concrete.
[0041] Example 9 A construction waste recycled aggregate concrete, which is different from Example 1 in that 2 kg of fly ash is further added to the raw materials of this example, and the preparation includes the following steps: (1) Weighing the raw material components, adding 26 kg of cement, 9 kg of crushed stone, 2 kg of fly ash, 3 kg of calcium silicate and 10 kg of water, and mixing and stirring to obtain a primary mixture; (2) Add 17.5 kg of the modified recycled aggregate prepared in Preparation Example 1, 0.3 kg of a polycarboxylic acid-based high-efficiency water reducing agent, 4 kg of polyacrylonitrile fiber and the remaining 10 kg of water to the primary mixture and mix well to obtain the construction waste recycled aggregate concrete.
[0042] Example 10 A construction waste recycled aggregate concrete, which is different from Example 1 in that 3 kg of slag is further added to the raw materials of this example, and the preparation includes the following steps: (1) Weighing the raw material components, adding 26 kg of cement, 9 kg of crushed stone, 3 kg of slag, 3 kg of calcium silicate and 10 kg of water, and mixing and stirring to obtain a primary mixture; (2) Add 17.5 kg of the modified recycled aggregate prepared in Preparation Example 1, 0.3 kg of a polycarboxylic acid-based high-efficiency water reducing agent, 4 kg of polyacrylonitrile fiber and the remaining 10 kg of water to the primary mixture and mix well to obtain the construction waste recycled aggregate concrete.
[0043] Comparative Example Comparative Example 1 A construction waste recycled aggregate concrete, which is different from Example 1 in that the recycled aggregate added in this comparative example is not modified.
[0044] Comparative Example 2 A construction waste recycled aggregate concrete, which is different from Example 1 in that the modified recycled aggregate used in this comparative example is prepared by Comparative Preparation Example 1.
[0045] Comparative Example 3 A construction waste recycled aggregate concrete, which is different from Example 1 in that the modified recycled aggregate used in this comparative example is prepared by Comparative Preparation Example 2.
[0046] Performance testing Detection method / test method The 7d and 28d compressive strength and splitting tensile strength of hardened concrete were tested according to the test method of the national standard GB / T50081-2019 "Standard for Test Methods of Mechanical Properties of Ordinary Concrete". The test specimens were formed using a 100mm×100mm×100mm mold and mechanically vibrated for 10s, and then cured to the specified age for test.
[0047] Table 1 Test data Combining Examples 1-3 and Comparative Example 1 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Example 1, indicating that the modification of the recycled aggregate can improve the structure of the interface transition zone between the recycled aggregate and the cement mortar, improve the density and bonding strength of the interface transition zone, and thus improve the compressive strength and splitting tensile strength of the concrete.
[0048] Combining Examples 1-3 with Comparative Examples 2-3 and Table 1, it can be seen that the experimental data of Examples 1-3 are better than those of Comparative Examples 2-3, indicating that pre-activation of the recycled aggregate with nanocellulose and further modification with alkyl ketene dimer can greatly improve the performance of the recycled aggregate and improve the compatibility between the recycled aggregate and the remaining raw materials, thereby improving the compressive strength and splitting tensile strength of the concrete.
[0049] It can be seen from Examples 1-4 and Table 1 that the experimental data of Examples 1-3 are better than those of Example 4, indicating that the selection of resin materials affects the modification effect on the recycled aggregate. The use of polyurethane as the resin material can react with the hydroxyl groups on the surface of the modified recycled aggregate to form polyurethane chemical bonds, thereby bonding with the remaining raw materials in the concrete to increase the connection strength, thereby improving the mechanical properties of the concrete.
[0050] Combining Example 1 with Examples 5-7 and Table 1, it can be seen that the experimental data of Examples 5-7 are better than those of Example 1, indicating that rare earth ferrosilicon powder can further fill cracks in recycled aggregate, improve its structural defects, and increase its strength, thereby improving the performance of concrete.
[0051] Combining Example 1 with Examples 8-10 and Table 1, it can be seen that the experimental data of Examples 8-10 are better than those of Example 1, indicating that the addition of active admixtures can further fill the pores in the interface transition zone, improve the microstructure at the interface, and improve the compressive strength of concrete.
[0052] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A construction waste recycled aggregate concrete, characterized in that: The composition comprises the following raw materials in parts by weight: 15-20 parts of modified recycled aggregate, 3-5 parts of polyacrylonitrile fiber, 0.2-0.4 parts of polycarboxylic acid-based high-efficiency water reducing agent, 2-4 parts of calcium silicate, 26-30 parts of cement, 16-22 parts of water, and 8-10 parts of crushed stone. The modified recycled aggregate is recycled aggregate modified by alkyl ketene dimer.
2. The construction waste recycled aggregate concrete according to claim 1, characterized in that: The modified recycled aggregate preparation comprises the following steps: (1) treating the regenerated aggregate by soaking it in a strong acid to obtain acidified regenerated aggregate, washing and drying it, adding a nanocellulose suspension to react for 2-3 hours to obtain activated regenerated aggregate; (2) The resin material and the alkyl ketene dimer are uniformly mixed and dispersed in water, and the activated recycled aggregate is placed in the water for stirring reaction for 2-3 hours. After natural air drying and curing, the mixture is ground and sieved to obtain the modified recycled aggregate.
3. The construction waste recycled aggregate concrete according to claim 2, characterized in that: The weight ratio of the recycled aggregate to the resin material, the powder and the alkyl ketene dimer added during the modification process is 2:1-1.2:0.2:0.1-0.5; The mass concentration of the nanocellulose suspension is 2-3 g / L.
4. The construction waste recycled aggregate concrete according to claim 2, characterized in that: In the step (2), 0.2-0.4 parts of rare earth ferrosilicon powder are also added.
5. The construction waste recycled aggregate concrete according to claim 2, characterized in that: The particle size of the modified recycled aggregate is 5-10 mm.
6. The construction waste recycled aggregate concrete according to claim 2, characterized in that: The resin material is polyurethane resin.
7. The construction waste recycled aggregate concrete according to claim 1, characterized in that: 1-3 parts of admixture material are also added to the raw materials, and the admixture material is any one of slag, volcanic ash or fly ash.
8. A method for preparing construction waste recycled aggregate concrete according to any one of claims 1 to 7, characterized in that: The steps include: (1) Weighing each raw material component, adding cement, crushed stone, calcium silicate and half of the water and mixing and stirring to obtain a primary mixture; (2) Adding modified recycled aggregate, polycarboxylic acid-based high-efficiency water reducing agent, polyacrylonitrile fiber and the remaining water to the primary mixture and stirring to obtain the construction waste recycled aggregate concrete.
Citation Information
Patent Citations
Recycled aggregate concrete and preparation method thereof
CN112811866A
Concrete containing construction waste and preparation method thereof
CN114380559A